2015
DOI: 10.3103/s1052618815080087
|View full text |Cite
|
Sign up to set email alerts
|

Electroplastic wire drawing: A promising method of production of lightweight wire and cable

Abstract: This paper presents the results of studies on the drawing of copper and steel wires by different technologies: conventional, warm (heated by alternating current), and electroplastic (under the action of pulsed current in the deformation zone) and an analysis of its structure and physicomechanical properties. As a result of the electroplastic drawing (EPD) of copper and steel wire, the drawing force is reduced by 30-35%, electrical resistance decreases by 18-20%, a more perfect axial texture arises, and the wir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Similarly, Troistskiy et at. [13] showed that, as compared to the CD process, wire plasticity was enhanced, and necessary drawing forces decreased by 30-35% and electrical resistance decreased by 18-20% during EPT of copper. Recently, Egea et al [14] analyzed the effect of EPT on drawing forces, mechanical behavior, and the microstructure of the material.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Troistskiy et at. [13] showed that, as compared to the CD process, wire plasticity was enhanced, and necessary drawing forces decreased by 30-35% and electrical resistance decreased by 18-20% during EPT of copper. Recently, Egea et al [14] analyzed the effect of EPT on drawing forces, mechanical behavior, and the microstructure of the material.…”
Section: Introductionmentioning
confidence: 99%
“…With the continuous progress in polymer science and manufacturing technology, man-made chemical fiber filaments such as polymer fibers [1,2], optical fibers [3,4], and wires and cables [5] have begun to play an increasingly important role in civil fabrics, communications, military industry, aerospace and other fields. In the spinning process, the appearance diameter uniformity of man-made chemical fiber filaments not only determines the quality classification and price of the filaments, but also when the appearance diameter uniformity is poor, the filaments strength will decrease and the breakage rate * Author to whom any correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…In the subsequent years, two main groups started to investigate the effect of electrical current on the deformation of various metallic and non-metallic materials. Pioneering researches were conducted in the USA by Conrad and his team [2,3,4,5,6,7] and in the Soviet Union by Troitskii and his people [8,9,10,11,12,13], who concluded that the enhancement of the formability and the reduction of the forming forces cannot be ascribed solely to the joule heating but also to an a-thermal effect, which they called the Electroplastic Effect (EPE). The discovery of such effect has led to a new way of forming metallic materials called Electrically Assisted Manufacturing (EAM), which is applied to a variety of processes such as rolling [14,15], drawing [8,16], cutting [16,17,18], forging [19,20], sintering [21,22], and bending [23,24], among others.…”
Section: Introductionmentioning
confidence: 99%